PERUBAHAN SPASIAL PERMUKIMAN TRADISIONAL DI DESA ADAT TENGANAN PEGRINGSINGAN BALI - I Wayan Mendra; Frysa Wiriantari (Jurnal Anala, 2016)
Traditional Balinese settlement is a full life and a round comprising three elements, namely: elements of the three elements celestial village manners (citizens), and Reef Village (region). Change is incident on a draft either intentional or not, to be different from the first because the influence of the outside and inside of himself. Spatial changes are changes that occur where the occurrence of changes in the function of traditional residential space formerly home residence temporary duplicated functions by not changing the main function as a traditional space. Modernity has contributed greatly to the change in the form of social and cultural. Tenganan Village People in the community have been changes in the spatial Pagringsingan that function concurrently traditional home goods store to sell souvenirs to tourists (as a tourism accommodation).This research approaches using qualitative descriptive analysis with data collection methods based on observations (observation, either directly or indirectly from the researcher to the object of research). This research was conducted in the village of Tenganan Indigenous Pegringsingan, District Manggis Karangasem Bali. From the research that has been done obtained three types of changes that occur in the traditional settlement community Tenganan Village People Pagringsingan namely: (a). Changes form (including changes in the physical building is the addition of a building from the main building), (b). Changes in the function of traditional houses that serve as a shop to sell souvenirs to tourists, causing blurring function is between traditional and modernity, (c). Changes in the shape and function of the building in the village There Tenganan Pagringsingan.Keywords : Traditional Settlement, Modernity, Spatial Changes